KAJIAN IMPLEMENTASI PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) DI DAERAH PENYANGGA TAMAN NASIONAL GUNUNG GEDE PANGRANGO (STUDI KASUS DI KAMPUNG SARONGGE DESA CIPUTRI KECAMATAN PACET KAB. CIANJUR) - Nurdianto, Ahmad; Susdiyanti, Tun; Supriyono, Bambang (Jurnal Nusa Sylva, 2014)
Forest management in National Park area are related to community development in the buffer zone . This provided an opportunity for stakeholders which is the company 's to contributing in national park preservation by Corporate Social Responsibility (CSR) program. This study aims to determine the form and implementation of CSR programs that have been implemented in the buffer zone of Gunung Gede Pangrango National Park, and to know perception and satisfaction of the local community about CSR program at Sarongge Resort. The main program of CSR program is adoption tree, beside that there are also community empowerment program. The results showed that CSR programs in Sarongge Resort still in charity. CSR implemented through a partnership between companies and Green Radio. Public perception of the CSR program is moderate. The level of people's satisfaction of CSR programs are less satisfied .